HIV patients developing primary CNS lymphoma lack EBV-specific CD4+ T cell function irrespective of absolute CD4+ T cell counts. - Gasser, O; Bihl, F; Wolbers, M; Loggi, E; Steffen, I; Hirsch, H; Günthard, H; Walker, B; Brander, C; Battegay, M; Hess, C (Public Library of Science, 2007)
BACKGROUND: In chronic HIV infection, antiretroviral therapy-induced normalization of CD4(+) T cell counts (immune reconstitution [IR]) is associated with a decreased incidence of opportunistic diseases. However, some individuals remain at risk for opportunistic diseases despite prolonged normalization of CD4(+) T cell counts. Deficient Epstein-Barr virus (EBV)-specific CD4(+) T cell function may explain the occurrence of EBV-associated opportunistic malignancy-such as primary central nervous system (PCNS) lymphoma-despite recovery of absolute CD4(+) T cell counts. METHODS AND FINDINGS: Absolute CD4(+) T cell counts and EBV-specific CD4(+) T cell-dependent interferon-gamma production were assessed in six HIV-positive individuals prior to development of PCNS lymphoma ("cases"), and these values were compared with those in 16 HIV-infected matched participants with no sign of EBV-associated pathology ("matched controls") and 11 nonmatched HIV-negative blood donors. Half of the PCNS lymphoma patients fulfilled IR criteria (defined here as CD4(+) T cell counts >or=500/microl blood). EBV-specific CD4(+) T cells were assessed 0.5-4.7 y prior to diagnosis of lymphoma. In 0/6 cases versus 13/16 matched controls an EBV-specific CD4(+) T cell response was detected (p = 0.007; confidence interval for odds ratio [0-0.40]). PCNS lymphoma patients also differed with regards to this response significantly from HIV-negative blood donors (p < 0.001, confidence interval for odds ratio [0-0.14]), but there was no evidence for a difference between HIV-negative participants and the HIV-positive matched controls (p = 0.47). CONCLUSIONS: Irrespective of absolute CD4(+) T cell counts, HIV-positive patients who subsequently developed PCNS lymphoma lacked EBV-specific CD4(+) T cell function. Larger, ideally prospective studies are needed to confirm these preliminary data, and clarify the impact of pathogen-specific versus surrogate marker-based assessment of IR on clinical outcome.